Epichloë Fungal Endophytes Influence Seed-Associated Bacterial Communities - Bastías, Daniel A.; Bustos, Ludmila Bubica; Jáuregui, Ruy; Barrera, Andrea; Acuña-Rodríguez, Ian S.; Molina-Montenegro, Marco A.; Gundel, Pedro E. (Frontiers in Microbiology, 2022)
Seeds commonly harbour diverse bacterial communities that can enhance the fitness of future plants. The bacterial microbiota associated with mother plant’s foliar tissues is one of the main sources of bacteria for seeds. Therefore, any ecological factor influencing the mother plant’s microbiota may also affect the diversity of the seed’s bacterial community. Grasses form associations with beneficial vertically transmitted fungal endophytes of genus Epichloë. The interaction of plants with Epichloë endophytes and insect herbivores can influence the plant foliar microbiota. However, it is unknown whether these interactions (alone or in concert) can affect the assembly of bacterial communities in the produced seed. We subjected Lolium multiflorum plants with and without its common endophyte Epichloë occultans (E+, E-, respectively) to an herbivory treatment with Rhopalosiphum padi aphids and assessed the diversity and composition of the bacterial communities in the produced seed. The presence of Epichloë endophytes influenced the seed bacterial microbiota by increasing the diversity and affecting the composition of the communities. The relative abundances of the bacterial taxa were more similarly distributed in communities associated with E+ than E- seeds with the latter being dominated by just a few bacterial groups. Contrary to our expectations, seed bacterial communities were not affected by the aphid herbivory experienced by mother plants. We speculate that the enhanced seed/seedling performance documented for Epichloë-host associations may be explained, at least in part, by the Epichloë-mediated increment in the seed-bacterial diversity, and that this phenomenon may be applicable to other plant-endophyte associations.